2020
DOI: 10.1007/s43440-020-00176-1
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the possible role of vitamin C in management of COVID-19

Abstract: The mainstay of management of coronavirus disease 2019 (COVID-19) is mainly supportive as to date there is no effective antiviral treatment, apart from remdesivir which has been approved by Food and Drug administration (FDA) for treatment of COVID-19, or vaccine. Supplementation with micronutrients, such as vitamins and minerals, has gained an increasing interest as part of the supportive management of COVID-19. Vitamin C levels in serum and leukocytes are depleted during the acute stage of infection owing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 105 publications
1
97
0
5
Order By: Relevance
“…Vitamin C has been reported to have multiple pharmacological characteristics, including antiviral, antioxidant, anti-inflammatory and immunomodulatory effects, which establish it as a potential therapeutic option in the management of COVID-19 ( 57 , 58 ). Indeed, previous studies have shown promising results when intravenously applying high doses of vitamin C for the management of COVID-19 ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C has been reported to have multiple pharmacological characteristics, including antiviral, antioxidant, anti-inflammatory and immunomodulatory effects, which establish it as a potential therapeutic option in the management of COVID-19 ( 57 , 58 ). Indeed, previous studies have shown promising results when intravenously applying high doses of vitamin C for the management of COVID-19 ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological effects of Vitamin C that could make it a potential option for prevention and treatment of COVID-19 have recently been reviewed [ 169 ]. Clinicians using intravenous Vitamin C in severely ill COVID-19 patients have reported positive clinical effects upon administration of 3 g every 6 h, together with steroids and anti-coagulants [ 170 ].…”
Section: Rationale For Antioxidant and Anti-inflammatory Therapiesmentioning
confidence: 99%
“…In the context of the ongoing COVID-19 pandemic and while there is still no effective antiviral therapy, this antiviral hallmark has a new significance. In this regard, many authors have reported a strong affinity between the beneficial properties of AA towards the complex pathological onset due to SARS-CoV-2 infection [ 118 , 119 , 120 , 121 , 122 ]. In this context, vitamin C seems to act in several ways as a polyfunctional molecule.…”
Section: Vitamin Cmentioning
confidence: 99%